Subordinate Actors’ Institutional Maintenance in Response to Coercive Reforms - Xiao, Q.; Klarin, Anton (2021)
Institutional work research shows how actors purposively create, maintain, and disrupt institutions. Failed or unintended consequences of institutional maintenance remain relatively unexplored, for two reasons. First, the role of coercive disruption actors (e.g., a state) has not been fully explored. Second, existing literature takes scant account of power and disregards the resistance tactics of subordinate actors. Drawing on a longitudinal case study of a migrant workers’ union in China, we show how subordinate actors were first able to maintain institutional arrangements followed by a maintenance failure under the disruption work performed by the authoritarian state. This study extends the institutional maintenance literature in two ways. First, subordinate actors can sustain institutions insofar as they collectively deploy superficial deference and hidden forms of resistance. Second, maintenance work is vulnerable in the sense that it is contingent on the systems of domination and the level of pressure exerted by the disruption actors.